Mitigation of radiation-induced esophageal fibrosis by macrophage-targeted phosphatidylserine-containing liposomes with partial PEGylation - Gyeung Mi Seon; In Gul Kim; Sun Woo Um; Eun-Jae Chung; Hyeong-Cheol Yang (Bioactive Materials)
Radiation-induced fibrosis (RIF) is a major complication following radiotherapy treatment. Macrophages are the key regulators of inflammatory responses and have emerged as critical targets for the prevention of fibrosis. This study evaluated the efficacy of PEGylated phosphatidylserine-containing liposomes (PEG-PSLs) in mitigating RIF by modulating macrophage activity. PEG-PSLs influenced the polarization of bone marrow-derived macrophages (BMDMs), reducing the expression levels of inflammatory cytokines and fibrosis-associated markers. These effects were observed within a specific PEGylation range, with the greatest reduction achieved at 1–1.5mol% PEG. Analysis of the IL-4-induced JAK-STAT signaling pathway indicated that the PEG-PSL-mediated suppression occurred at or beyond the point of JAK-1 phosphorylation. In in vitro fibrosis assays, PEG-PSLs reduced fibroblast-to-myofibroblast and epithelial-to-mesenchymal transitions when co-cultured with BMDMs. In vivo studies using a rat model of esophageal irradiation demonstrated that PEG-PSLs effectively attenuated fibrotic progression, preserved tissue architecture, and enhanced muscle regeneration. These findings indicate the potential of partially PEGylated phosphatidylserine liposomes as therapeutic agents for mitigating post-irradiation esophageal fibrosis.